Penetrance of Craniofacial Anomalies in Mouse Models of Smith-Magenis Syndrome Is Modified by Genomic Sequence Surrounding Rai1: Not All Null Alleles Are Alike - Yan, Jiong (The American Society of Human Genetics, 2007)
Craniofacial abnormality is one of the major clinical manifestations of Smith-Magenis syndrome (SMS). Previous analyses in a mixed genetic background of several SMS mouse models—including Df(11)17/+ and Df(11)17-1/+, which have 2-Mb and 590-kb deletions, respectively, and Rai1(−/+)—revealed that the penetrance of the craniofacial phenotype appears to be influenced by deletion size and genetic background. We generated an additional strain with a 1-Mb deletion intermediate in size between the two described above. Remarkably, the penetrance of its craniofacial anomalies in the mixed background was between those of Df(11)17 and Df(11)17-1. We further analyzed the deletion mutations and the Rai1(−/+) allele in a pure C57BL/6 background, to control for nonlinked modifier loci. The penetrance of the craniofacial anomalies was markedly increased for all the strains in comparison with the mixed background. Mice with Df(11)17 and Df(11)17-1 deletions had a similar penetrance, suggesting that penetrance may be less influenced by deletion size, whereas that of Rai1(−/+) mice was significantly lower than that of the deletion strains. We hypothesize that potential trans-regulatory sequence(s) or gene(s) that reside within the 590-kb genomic interval surrounding Rai1 are the major modifying genetic element(s) affecting the craniofacial penetrance. Moreover, we confirmed the influence of genetic background and different deletion sizes on the phenotype. The complicated control of the penetrance for one phenotype in SMS mouse models provides tools to elucidate molecular mechanisms for penetrance and clearly shows that a null allele caused by chromosomal deletion can have different phenotypic consequences than one caused by gene inactivation.